Serological confirmation of Borrelia burgdorferi infection in dogs in the Czech Republic - Pejchalová, K; Zákovská, A; Fucík, K; Schánilec, P (Veterinary research communications, 2006)
From the epidemiological point of view, dogs are very important since they are considered a suitable indicator of the spread of human borreliosis. Serum samples obtained from healthy, asymptomatic military dogs from 12 different areas in the Czech Republic were examined for IgG antibodies to Borrelia burgdorferi sensu lato (s.l.). The total of 399 serum samples were tested by a whole-cell ELISA. Specific antibodies to Borrelia burgdorferi s.l. were detected in 26 cases (6.5%). In different localities, the seroprevalence varied from 0.0% to 28.6%. Two local isolated strains Br-75 (Borrelia afzelii) and Br-97 (Borrelia garinii) were used as antigens. A total of 22 (5.5%) were positive for antibodies to Borrelia afzelii and 19 (4.8%) were positive for antibodies to Borrelia garinii. Fifteen cases were positive for both antibodies. A significantly higher seroprevalence was found in younger dogs (1-3 years) than in older ones (p < 0.05). An analysis of seroprevalence by months of sampling showed no significant difference (p > 0.05).
Keywords: Česká republika; protilátky bakteriální; nemoci psů; Antibodies, Bacterial; Czech Republic; psi; Borrelia burgdorferi; lymeská nemoc; Serologic Tests; Animals; Seroepidemiologic Studies; séroepidemiologické studie; Dogs; sérologické testy; zvířata; Dog Diseases; Lyme Disease